THE RELATIONSHIP BETWEEN ISLAMIC BUSINESS STUDENTS AND¬ THE USE OF ISLAMIC BANKS - Kurniawan, Rifqi IR Caesario; Wiranatakusuma, Dimas Bagus (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
Today the development of Islamic banking has begun to gain public trust as customers of Islamic banks. Indonesia as a country with a Muslim community can encourage the advancement of Islamic banking. The development of Islamic banking cannot be separated from the understanding possessed by each generation in its time. The understanding possessed will affect the growth of the Islamic banking sector, cannot be separated from the role of students who study Islamic banking in using Islamic banks. This study entitled THE RELATIONSHIP BETWEEN ISLAMIC BUSINESS STUDENTS AND THE USE OF ISLAMIC BANKS aims to determine whether there is a relationship between students studying Islamic economics with their interest in using Islamic banks as accounts. This study uses a quantitative method by distributing questionnaires to student respondents at various universities in Indonesia. The results of the questionnaires that have been filled in by respondents were analyzed using SPSS 25 software with a quantitative descriptive method. The results of this study have a strong positive correlation on independent variables: variables X1 (Learning Islamic Economics), variables X2 (Information Sources), and variables X3 (Sources of Advice) on dependent variable Y (Interest in Using Islamic Banks). This study ensures that knowledge can encourage student interest in using Islamic banks.